Family involvement in the end-of-life decisions of competent intensive care patients. (February 2013) - Lind, Ranveig; Nortvedt, Per; Lorem, Geir; Hevrøy, Olav
In this article, we report the findings from a qualitative study that explored how relatives of terminally ill, alert and competent intensive care patients perceived their involvement in the end-of-life decision-making process. Eleven family members of six deceased patients were interviewed. Our findings reveal that relatives narrate about a strong intertwinement with the patient. They experienced the patients' personal individuality as a fragile achievement. Therefore, they viewed their presence as crucial with their primary role to support and protect the patient, thereby safeguarding his values and interests. However, their inclusion in decision making varied from active participation in the decision-making process to acceptance of the physicians' decision or just receiving information. We conclude that models of informed shared decision making should be utilised and optimised in intensive care, where nurses and physicians work with both the patient and his or her family and regard the family as partners in the process.